Dampak Budaya “Bejamu Saman” Bagi Masyarakat di Kabupaten Gayo Lues - Hamzali, Said (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Dance is one of the most diverse cultural assets in Indonesia. Indonesia is a country rich in culture from each region. The people of Gayo Lues Regency have a traditional art, namely bejamu saman. Bejamu saman is an art event of the Gayo Lues community, this bejamu saman is done by inviting people from other villages to come to perform the saman dance alternately, but in its implementation, both villages will show their prowess in playing the saman alternately. This study aims to determine: the impact of the bejamu saman culture on the people of Gayo Lues Regency. The method used in this study is a descriptive - qualitative method. The data sources in this study consist of primary and secondary data sources. The data analysis pattern that will be used in this study is ethnography. The results of the study indicate that the positive impact of the bejamu saman culture on the people of Gayo Lues is to improve the economy, increase social integration, and maintain the stability of Gayo culture, while the negative impacts often occur ikhtilat and genit rante.